Philosophical problem of relations according to Peirce – alliances towards an ontology of relations regarding two aspects of Synechism - Cardoso Jr., Hélio Rebello; Ferraz, Thien Spinelli (Cognitio-Estudos: revista eletrônica de filosofia, 2012)
This paper aims to present Peirce’s philosophy as an alternative to the philosophy of being. Peirce’s ontology could not be ranked as a discourse about the reality of being (Aristotle); nor could it be understood as a scientific metaphysics ruled by transcendental conditions (Kant). Peirce evades from both traditions, as long as he builds his ontology from a semiotics-based reality whose mode of being is defined in terms of relations (monadic, dyadic and triadic relations). So I assume through my argument that Peirce’s ontology forges an essential alliance to the so-called ontology of relations (BAINS, 2006). I summarize the allies and principles of such ontology, and consequently I argue for Peirce’s part on it taking into account two elements of his Synechism: the primacy of relations over individuals in continuous multiplicities and the mode of being of relations according to triadic relations in the category of Thirdness.